Synthesis and structural characterization of homochiral 2D coordination polymers of zinc and copper with conformationally flexible ditopic imidazolium-based dicarboxylate ligands - Nicasio, Antonio I.; Montilla, Francisco; Álvarez, Eleuterio; Pérez-Colodrero, Rosario Mercedes; Galindo, Agustín (The Royal Society of Chemistry, 2016)
Different novel coordination polymers containing zinc, 1–4, and copper, 5–8, metals, connected via chiral imidazolium-based dicarboxylate ligands, [LR]−, were isolated by reaction between zinc acetate or copper acetate and enantiomerically pure HLR compounds. They were characterised and structurally identified by X-ray diffraction methods (single crystal and powder). These compounds are twodimensional homochiral coordination polymers, [M(LR)2]n, in which the metal ions are coordinated by the two carboxylate groups of [LR]− anions in a general bridging monodentate μ2–κ1-O1,κ1-O3 fashion that afforded tetrahedral metal coordination environments for zinc, 1–4, and square planar for copper, 5–8, complexes. In all the compounds the 3D supramolecular architecture is constructed by non-covalent interactions between the hydrophobic parts (R groups) of the homochiral 2D coordination polymers and, in some cases, by weak C–H⋯O non-classical hydrogen bonds that provided, in general, a dense crystal packing. DFT calculations on the [LR]− anions confirmed their conformational flexibility as ditopic linkers and this fact makes possible the formation of different coordination polymers for four-coordinated metal centers. Preliminary studies on the Zn-catalyzed synthesis of chiral α-aminophosphonates were carried out and, unfortunately, no enantioselectivity was observed in these reactions.
Keywords: Química inorgánica; 2D coordination polymers; X-ray diffraction; Zinc and copper; Imidazolium-based dicarboxylate